PENGEMBANGAN BAHAN AJAR TEMATIK BERBASIS KEARIFAN LOKAL PATI TEMA â€œDAERAH TEMPAT TINGGALKUâ€ PADA SISWA KELAS IV SEKOLAH DASAR - Dewinta Asmorowati; Slamet Utomo; Sri Surachmi (Universitas Muria Kudus, 2021)
The purpose of this study 1) To find the need for thematic teaching materials based on Pati local wisdom with the theme of â€œDaerah tempat Tinggalkuâ€ in grade IV elementary school students, 2) to produce prototypes of thematic teaching materials based on Pati local wisdom and 3) to describe the appropriateness of thematic teaching materials based on PatiÂ local wisdom with theme â€œ Daerah Tempat Tinggalkuâ€. The research method used by Research & Development with 7 stages of research includes potential and problems, data collection, design, validation, revision, testing, and revision of the final product. The result of research based on interviews and observations is the need for a companion book that is suitable for student development and based on Pati's local wisdom. The prototype of this book contains an introduction, contents based on Pati local wisdom, and a closing. The results of the validation by content experts were 23.3 or 78% and the design experts scored 28.2 or 81%. 84% of teachers agree that the use of teaching materials and student learning outcomes increases. Based on these data, it can be concluded that the thematic teaching materials based on Pati local wisdom on the theme â€œDaerah tempat Tinggalkuâ€ are very suitable to be used as a companion book for students from the Government in grade IV of Elementary School.